An Anomaly in Political Recruitment: The Logic of Cross Candidacy in 2020 Jambi Provincial-Local Election - Syaiful Bahri (Politicon : Jurnal Ilmu Politik, 2022)
When political parties are more open in political recruitment, anomalies sometimes occur, as happened in the 2020 Jambi local election (Pilkada). Political parties nominated other party cadres as candidates and produce the phenomenon of cross candidacy. By conducting a document study in qualitative research, this article finds that cross candidacy occurs because the nomination system is not in line with the multi-party system and the proportional electoral system. In response, the rules of political parties have become more elastic. This phenomenon is also influenced by the dynamics between internal party actors at the regional level even though decision-making is ultimately centralized. Cross candidacy is also supported by the perception that the Pilkada takes place as a contestation of candidate figures rather than a representation of the ideology and platform of political parties.